Separating arterial pressure increases and decreases in assessing cardiac baroreflex sensitivity via sequence and bivariate phase-rectified signal averaging techniques. - De Maria, Beatrice; Bari, Vlasta; Ranucci, Marco; Pistuddi, Valeria; Ranuzzi, Giovanni; Takahashi, Anielle C. M.; Catai, Aparecida M.; Dalla Vecchia, Laura; Cerutti, Sergio; Porta, Alberto (Medical & Biological Engineering & Computing, 2018)
Cardiac baroreflex (cBR) is activated by both arterial pressure (AP) increases and decreases. Sequence method, a widely utilized tool assessing cBR sensitivity (cBRS) from spontaneous heart period (HP) and systolic AP (SAP) variations, allows the separated computation of cBRS from positive and negative SAP variations. The recently proposed phase-rectified signal averaging (PRSA) method has the same feature but it has been applied so far solely to positive SAP variations. We adapted the PRSA method to compute cBRS over negative SAP variations and we compared the results with those derived from sequence method over two protocols: (i) graded head-up tilt (HUT) at 15, 30, 45, 60, and 75° in 19 healthy subjects and (ii) general anesthesia induction in 118 patients undergoing coronary artery bypass graft surgery. Regardless of the sign of SAP changes and method, cBRS moved toward 0 during HUT. Only sequence method detected the cBRS decrease after general anesthesia induction. In both protocols, the correlation between the PRSA-based cBRSs derived from positive and negative SAP changes was higher than that obtained from analogous sequence-based cBRSs and correlation between equivalent cBRSs derived from different methods might be absent. We conclude that the two methods are not interchangeable in assessing cBRS. Graphical abstract Graphical representation of the baroreflex sensitivity (BRS) estimation procedures carried out using sequence (SEQ) and phase-rectified signal averaging (PRSA) techniques over spontaneous fluctuations of heart period (HP) and systolic arterial pressure (SAP). BRSSEQ and BRSPRSA was separately computed over positive (+) and negative (-) SAP variations.